Degradation mechanisms of SiC/BN/SiC after low temperature humidity exposure. Issue 12 (September 2020) - Diaz, Oriol Gavalda; Marquardt, Katharina; Harris, Stephen; Gale, Louise; Vandeperre, Luc; Saiz, Eduardo; Giuliani, Finn
Abstract: The environmental degradation of SiC/BN/SiC CMCs under low temperature water exposure is still an unexplored field. This work shows how the effect of low temperature humid environments can be detrimental for turbostratic BN interphases, leading to a drop in mechanical properties. Furthermore, initial low-temperature humid environments can induce a faster degradation during subsequent thermal exposure. In order to understand how low temperature water exposure affects the CMC and how these changes affect the material response to subsequent exposures, intermediate temperature (800 °C) exposures have been studied before and after the low temperature humidity tests. The main challenge of this work consists of understanding how different constituents of the CMC structure (e.g. fibres and interphases) are degrading and consequently affecting the overall bulk mechanical performance and failure modes of the material. For this, linking the change in morphology and chemistry of the interphases with the micromechanical properties each constituent has been crucial.